Acceptability of mental health toolbox talk in primary health care service; a case study of Oshodi/ Isolo local government area, Lagos state, Nigeria - Silas, Usen J.; Dotimi, Doris A.; Oladunni, Rukayat (International Journal Of Community Medicine And Public Health, 2024)
Background: Mental health services at the primary healthcare level remain at their lowest ebb in most developing countries. Mental health toolbox talk is a way to solve mental health needs in the community. This study aimed at assessing the acceptability of mental health toolbox talk in primary health care (PHC), in Oshodi/Isolo, local government area (LGA). Methods: This is a descriptive cross-section study conducted among 119 PHC staff. A multistage sampling technique was used to select participants for the study. Data were collected and analyzed using the statistical package for social sciences (SPSS) 26 and the EPI Info application. Result: Findings revealed that the majority 79% of respondents were females and were within the age range of 40-60 years of age. Also, 76% of PHC staff showed poor knowledge of mental management, while 94% of the respondents accepted the integration of mental health toolbox talk into PHC. Findings revealed that professions (χ2=12.998, p<0.05) had a significant association with the respondents’ knowledge about mental health. However, the analysis of variance shows there is a statistically insignificant difference in knowledge between the professional groups of PHC staff on the provision of mental health services in the PHC facilities, (f=0.616; p=0.688) (p>0.05). Conclusions: Lack of knowledge on mental health was observed to mitigate PHC staff in the management of mental health disorders, and the need for training on mental health toolbox talk was determined.